Pelatihan Penulisan Ilmiah dan Populer di Era Digital di Desa Bekonang, Kecamatan Mojolaban, Kabupaten Sukoharjo - Alkhajar, Eka Nada Shofa; Wijaya, Sri Herwindya Baskara; Luthfia, Agusniar Rizka (Bakti Cendana, 2023)
The ability to write in both scientific and popular forms is an important skill in the digital era. The main goal is to be able to contribute in spreading positive messages to a wider audience. The community service in the form of training aims to provide writing skills to community service target. Based on the situation analysis that has been carried out, the community service team found that the target requires a writing course or training related to it. The methods used in this community service are lectures, discussions and mentoring. The target of community service participated the training with great enthusiasm. The results achieved from this community service is that the target had good knowledge and skills to write in scientific and popular forms.